PEMBENTUKAN POKDARWIS DAN PELATIHAN BAHASA INGGRIS SEBAGAI UPAYA PENINGKATAN CITRA DESA WISATA TIMUHUN KECAMATAN BANJARANGKAN KLUNGKUNG - I WAYAN SUARDANA; IB. ASTINA; MADE KUSUMA NEGARA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2007)
ABSTRACT Tourism conscious group become alternative start development tourism in Timuhun village. All these basin of activity start from planning come up with tourism observation in ambulatory Timuhun village better and more comprehensive. As effort of improvement of human resource quality done by training of English and conscious counseling of tour. This activity is ambulatory better as according to expected target. Role and also stakeholders earn to share better, as a mean to realize Timuhun as rural tourist in Klungkung.